2020
DOI: 10.3390/v13010019
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Human Coronavirus by Titania Nanoparticle Coatings and UVC Radiation: Throwing Light on SARS-CoV-2

Abstract: The newly identified pathogenic human coronavirus, SARS-CoV-2, led to an atypical pneumonia-like severe acute respiratory syndrome (SARS) outbreak called coronavirus disease 2019 (abbreviated as COVID-19). Currently, nearly 77 million cases have been confirmed worldwide with the highest numbers of COVID-19 cases in the United States. Individuals are getting vaccinated with recently approved vaccines, which are highly protective in suppressing COVID-19 symptoms but there will be a long way before the majority o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 54 publications
2
87
0
2
Order By: Relevance
“…SARS-CoV-2 can be inactivated by other methods, such as light-activated coatings[ 62 ], ultraviolet (UV) light [ [63] , [64] , [65] ], atmospheric cold plasma [ 12 ], heat treatment [ 66 ], and ozone [ 67 ].…”
Section: Other Methods For Inactivating Sars-cov-2 At Surfacesmentioning
confidence: 99%
“…SARS-CoV-2 can be inactivated by other methods, such as light-activated coatings[ 62 ], ultraviolet (UV) light [ [63] , [64] , [65] ], atmospheric cold plasma [ 12 ], heat treatment [ 66 ], and ozone [ 67 ].…”
Section: Other Methods For Inactivating Sars-cov-2 At Surfacesmentioning
confidence: 99%
“…In this regard, in a study, the photocatalytic performance of nano-TiO 2 was explored for the deactivation of coronavirus through UV radiation for application in grocery stores as well as hospitals. 49 Nano-TiO 2 particles were deposited on glass coverslips and the results showed good virucidal efficacy. This study confirmed the effectiveness of TiO 2 -coated surfaces for the disinfection of coronaviruses.…”
Section: The Role Of Tio 2 Nanoparticles During the Covid-19 Crisismentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel human coronavirus that causes coronavirus disease 2019 (COVID- 19), which has had an unprecedented impact on modern human civilization [1] and resulted in more than 1.7 million deaths globally, as of late December 2020. SARS-CoV-2 belongs to a group of pathogenic enveloped viruses with positive single stranded RNA genomes encoding spike (S), envelope (E), membrane (M), and nucleocapsid (N) proteins, which are structural proteins required for producing structurally complete viral particles, and nonstructural proteins [2].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic reaction of titanium dioxide (TiO 2 ) is useful for disinfecting surfaces, air, and water. Indeed, the photocatalytic reaction of TiO 2 kills microorganisms, such as bacteria and fungi, and inactivates influenza virus, hepatitis C virus, vesicular stomatitis virus, enterovirus, herpes virus, Zika virus, human coronavirus, bovine coronavirus, human norovirus, murine norovirus, SARS coronavirus, and bacteriophage [16][17][18][19][20][21][22][23]. Furthermore, it has previously been reported that phage B1 present in aerosols are effectively inactivated by the photocatalytic reaction of TiO 2 [24].…”
Section: Introductionmentioning
confidence: 99%